Effects of Exercise or Mechanical Stimulation on Bone Development and Bone Repair - Lidan Song (Stem Cells International)
The development and regeneration of the bone are tightly regulated by mechanical cues. Multiple cell types, including osteoblasts, osteocytes, osteoclasts, mesenchymal stem cells (MSCs), and recently found skeletal stem cells (SSCs), are responsible for efficient bone development and injury repair. The immune cells in the environment interact with bone cells to maintain homeostasis and facilitate bone regeneration. Investigation of the mechanism by which these cells sense and respond to mechanical signals in bone is fundamental for optimal clinical intervention in bone injury healing. We discuss the effects of exercise programs on fracture healing in animal models and human patients, which encouragingly suggest that carefully designed exercise prescriptions can improve the result of fracture healing during the remodeling phase. However, additional clinical tracing and date accumulation are still required for the pervasive application of exercise prescriptions to improve fracture healing.